Fabrication of an Ion-sensitive in situ Gel loaded with Nanostructured Lipid Carrier for Nose to Brain Delivery of Donepezil - Butani, Dr. Shital (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: The purpose of the present study was to formulate in situ gelling formulation combining nanostructured lipid carrier of donepezil and an ionic-triggered gellan gum matrix following intranasal administration for the treatment of Alzheimer’s disease. Materials and Methods: Donepezil-loaded lipid carrier was prepared by a melt emulsification-probe sonication method, optimized, and characterized. Nanostructured lipid carrier was incorporated into gellan gum-based in situ gel and characterized for in situ gelling properties, rheological properties, and texture analysis. The developed formulation was evaluated in vivo through pharmacodynamic and pharmacokinetic study in rats. Results and Discussion: In vivo efficacy tested in scopolamine-induced amnesia model indicated a significant improvement in cognitive function in rat treated with in situ gel as compared to the marketed formulation. A pharmacokinetic study showed the higher drug distribution in brain and lower drug concentration in plasma from a developed formulation which indicates its higher safety and efficacy through a nasal route. Conclusion: Thus, nanostructured lipid carrier-based in situ gel administered through intranasal route can be clinically promising approach for enhancing efficacy through the brain and reducing toxicity to other organs.